Hyaluronic acid gel mixture as well as preparation method and application thereof

By dispersing crosslinked sodium hyaluronate gel particles in disulfide bond crosslinked sodium hyaluronate gel to form an integrated gel, the problem of degradation of cohesion of crosslinked hyaluronate gel in the prior art is solved, high cohesion and high elasticity are achieved, and suitable for the preparation of prosthetic materials.

CN119868661AActive Publication Date: 2025-04-25BIOREGEN BIOMEDICAL (CHANGZHOU) CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510371478.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-27
Publication Date
2025-04-25
Estimated Expiration
2045-03-27

AI Technical Summary

Technical Problem

In clinical applications, existing crosslinked hyaluronic acid gels are difficult to have high elasticity and high cohesion due to their reduced cohesion in clinical applications, which affects their supporting performance and stability as prosthetic material.

Method used

By dispersing crosslinked sodium hyaluronate gel particles in disulfide crosslinked sodium hyaluronate gel, an integrated gel is formed, and combined with the method of shear strain testing, the gel is ensured with high cohesion and high elasticity.

Benefits of technology

The high elastic modulus G´ in the linear viscoelastic region with shear strain γ=0.1% and shear frequency 1Hz is achieved, and the high viscosity modulus G´ is not less than 650Pa and the high viscosity modulus is not less than 70Pa, and has excellent anti-enzymatic modulus and biological stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
Patent Text Reader

Abstract

The invention discloses a hyaluronic acid gel mixture as well as a preparation method and application thereof, and belongs to the technical field of prosthetic materials, the hyaluronic acid gel mixture comprises disulfide bond cross-linked sodium hyaluronate gel and cross-linked sodium hyaluronate gel particles which are mixed, the cross-linked sodium hyaluronate gel particles are dispersed in the disulfide bond cross-linked sodium hyaluronate gel, and the hyaluronic acid gel mixture has high cohesion and high elasticity, has better enzymolysis resistance and stability, and is suitable for being applied to preparation of medical products, especially medical products used as prosthetic materials; the preparation method of the hyaluronic acid gel mixture comprises the following steps: dispersing sodium hyaluronate gel particles in a sodium hyaluronate sulfhydrylation derivative solution, then oxidizing the sodium hyaluronate sulfhydrylation derivative solution to form disulfide bond cross-linked sodium hyaluronate gel, and further obtaining the hyaluronic acid gel mixture. The preparation method of the hyaluronic acid gel mixture is simple and easy to operate, and is convenient for wide application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of prosthetic materials, and in particular to a hyaluronic acid gel mixture and a preparation method and application thereof. Background Art

[0002] Hyaluronic acid is a non-sulfonated glycosaminoglycan composed of repeating disaccharide units (α-1,4-D-glucuronic acid and β-1,3-N-acetyl-D-glucosamine), which exists in all connective tissues and has good biocompatibility and unique physical and chemical properties. However, due to its fluidity and rapid degradation by hyaluronidase in the body, its clinical application is limited.

[0003] In order to solve this problem, sodium hyaluronate is usually chemically cross-linked / modified, and the commonly used cross-linking agents are divinyl sulfoxide (DVS) and 1,4-butanediol diglycidyl ether (BDDE). The cross-linked hyaluronic acid gel prepared by the cross-linking reaction reduces the fluidity of hyaluronic acid and slows down its degradation and absorption rate in the body.

[0004] In the prior art, Chinese patent CN101056891A provides a method for preparing a cross-linked hyaluronic acid gel, wherein a mixture containing more than 10 W / V% of hyaluronic acid, a cross-linking agent (divinyl sulfone, 1,4-butanediol diglycidyl ether and ethylene glycol diglycidyl ether) and water is stirred and mixed under acidic (pH=1-5) or alkaline (pH=10-14) conditions. The gel prepared by this method has an excellent elastic modulus G´. U.S. Patent US4582865 discloses a cross-linked hyaluronic acid derivative using divinyl sulfone (DVS) as a cross-linking agent, and its hydrogel has good viscoelastic properties.

[0005] The cross-linked hyaluronic acid gel prepared by the above patented method through cross-linking reaction reduces the fluidity of hyaluronic acid and slows down its degradation and absorption rate in the body. However, in order to facilitate clinical use, these cross-linked hyaluronic acid gel products usually need to crush the hyaluronic acid gel into fine particles. However, such operation will lead to a decrease in the adhesion between the gel particles, that is, a decrease in the cohesion of the gel. In some medical applications, materials need to have good support, such as prosthetic materials. The support of the gel is usually determined by cohesion and elasticity. Cohesion represents the ability of the gel to maintain its original shape. The stronger the cohesion, the more resistant it is to external force extrusion and the less likely it is to spread. Elasticity represents the hardness of the gel itself. The higher the elasticity, the less likely it is to deform. For example, when it is used for medical cosmetic purposes, it is necessary to increase the volume of the skin or tissue, especially when shaping the dorsum of the nose and / or the root of the nose and the mandible, the material is required to have strong bone support properties to achieve a good plastic effect; when it is used for serious medical treatment purposes, such as applied to sphincter tissue to treat urinary incontinence, viscoelastic treatment of osteoarthritis, and soft tissue filling of metatarsalgia, the material is also required to have sufficient support properties. For example, eye surgeries such as sealing retinal holes to treat rhegmatogenous retinal detachment and vitreous filling to treat retinal detachment require materials to have overall high cohesion to prevent hyaluronic acid gel particles from blocking the tiny channels of the anterior and posterior chamber aqueous circulation. At the same time, the above clinical application scenarios all require materials to have high elasticity and high cohesion.

[0006] In order to solve this problem and achieve better injectability, one solution is to add a certain proportion of non-cross-linked hyaluronic acid to form a physically mixed two-phase gel, such as Restylane®, Durolane®, Pelane®, etc. They are prepared by homogenizing cross-linked hyaluronic acid and non-cross-linked hyaluronic acid and are used for facial filling or viscosity-increasing treatment of arthritis. This type of physically mixed two-phase gel improves the cohesion of the gel to a certain extent.

[0007] Another solution is to mix a cross-linked hyaluronic acid gel with better elasticity and a cross-linked hyaluronic acid gel with better viscosity. However, this can only produce a gel with a compromise between elasticity and viscosity, and it is impossible to improve the high viscosity of the gel without losing the high elasticity of the gel.

[0008] However, the above technology cannot improve the cohesion of the gel mixture without reducing the elastic modulus of the cross-linked hyaluronic acid gel, that is, it cannot have both high elasticity and high cohesion. Summary of the invention

[0009] The technical problem to be solved by the present invention is to provide a hyaluronic acid gel mixture and a preparation method and application thereof, wherein the hyaluronic acid gel mixture has high cohesion and high elasticity, and has good anti-enzymatic performance and stability, and is suitable for use in the preparation of medical products. The preparation method of the hyaluronic acid gel mixture is simple and easy to operate, and is convenient for wide application.

[0010] In order to solve the above technical problems, the first aspect of the present invention is to provide a hyaluronic acid gel mixture, comprising a mixed disulfide bond cross-linked sodium hyaluronate gel and cross-linked sodium hyaluronate gel particles, wherein the cross-linked sodium hyaluronate gel particles are dispersed in the disulfide bond cross-linked sodium hyaluronate gel; When the hyaluronic acid gel mixture is tested in a linear viscoelastic region with a shear strain of γ=0.1% and a shear frequency of 1 Hz, the elastic modulus G' of the hyaluronic acid gel mixture is not less than 650 Pa, and the viscous modulus is not less than 70 Pa.

[0011] In the present invention, the cross-linked sodium hyaluronate gel particles are dispersed in the disulfide cross-linked sodium hyaluronate gel, which means that the cross-linked sodium hyaluronate gel particles in the disulfide cross-linked sodium hyaluronate gel are wrapped by the disulfide cross-linked sodium hyaluronate gel, and the cross-linked sodium hyaluronate gel particles are dispersed in the colloid of the disulfide cross-linked sodium hyaluronate gel, and the two form an integrated gel.

[0012] In the present invention, the cross-linked sodium hyaluronate gel particles provide the mixture with high elastic support performance and resistance to enzymolysis due to their high elastic modulus, and also provide cohesion for the cross-linked sodium hyaluronate gel particles themselves; the disulfide bond cross-linked sodium hyaluronate gel provides the mixture with high cohesion and further increases the resistance to enzymolysis of the mixture.

[0013] The hyaluronic acid gel mixture provided by the present invention is an integrated gel as a whole, and the elastic modulus G' tested in the linear viscoelastic region of shear strain γ=0.1% and shear frequency 1Hz is not less than 650Pa, and the viscosity modulus is not less than 70Pa, with high cohesion and high elasticity, and excellent anti-enzymatic ability; the hyaluronic acid gel mixture provided by the present invention is compared with non-cohesive gel or gel composition, under high shear force, the cohesive gel can better maintain its shape and is not easy to deform, and because there is no need to add non-cross-linked sodium hyaluronate, the problem of reduced viscosity stability is avoided. After testing, the hyaluronic acid gel mixture provided by the present invention is subjected to high saturated steam for 10 to 20 minutes and 50°C for 9 months or 25°C for three years, and the gel composition does not significantly degrade or become unstable, which is specifically manifested as the gel composition continues to be placed at 50°C for 274 days after sterilization, and its dynamic viscosity retention value is above 90%. When the hyaluronic acid gel mixture provided by the present invention is used as a prosthetic material, its high cohesion and high elasticity make it have excellent mechanical properties, and its excellent resistance to enzymolysis makes it have good biological stability.

[0014] In a specific embodiment, the particle size of the cross-linked sodium hyaluronate gel particles ranges from 50 μm to 2500 μm.

[0015] In a specific embodiment, in the cross-linked sodium hyaluronate gel particles, D50 is not greater than 800 μm and / or D90 is not greater than 2000 μm.

[0016] In a specific embodiment, the hyaluronic acid content in the cross-linked sodium hyaluronate gel particles is 12-50 mg / mL or 16-30 mg / mL; the hyaluronic acid content in the disulfide cross-linked sodium hyaluronate gel is 0.2-10 mg / mL or 0.5-4 mg / mL.

[0017] In a specific embodiment, the cross-linking degree of the cross-linked sodium hyaluronate gel particles is 1.0% to 20%; the cross-linking degree of the disulfide bond cross-linked sodium hyaluronate gel is 0.05% to 2.5% or 0.1% to 1.0%.

[0018] In a specific embodiment, the mass ratio of the cross-linked sodium hyaluronate gel particles to the disulfide bond cross-linked sodium hyaluronate gel is 19:1 to 1:1.

[0019] In order to solve the above technical problems, the second aspect of the present invention is to provide the application of the aforementioned hyaluronic acid gel mixture in the preparation of medical products. Understandably, since the hyaluronic acid gel mixture provided by the present invention has high cohesion and high elasticity and excellent anti-enzymatic ability, it is suitable for use in the preparation of medical products, especially prosthetic materials, etc., for example, it is used to prepare products for blocking retinal holes to treat rhegmatogenous retinal detachment, products for preparing vitreous filling, products for preparing viscoelastic treatment of osteoarthritis, products for preparing soft tissue filling wrinkles, products for preparing facial reshaping products, and products for preparing products to increase sphincter volume.

[0020] In order to solve the above technical problems, the third aspect of the present invention is to provide a method for preparing the aforementioned hyaluronic acid gel mixture, comprising the following steps: S1. crushing the cross-linked sodium hyaluronate gel into cross-linked sodium hyaluronate gel particles; S2, dispersing the cross-linked sodium hyaluronate gel particles obtained in step S1 in a solution of a thiolated sodium hyaluronate derivative; S3. The sodium hyaluronate thiolated derivative solution dispersed with cross-linked sodium hyaluronate gel particles obtained in step S2 is gradually subjected to an oxidation process to form a disulfide-cross-linked sodium hyaluronate gel, thereby obtaining a hyaluronic acid gel mixture, wherein the elastic modulus G' of the hyaluronic acid gel mixture tested in the linear viscoelastic region with a shear strain γ=0.1% and a shear frequency of 1 Hz is not less than 650 Pa, and the viscosity modulus is not less than 70 Pa.

[0021] In the present invention, the cross-linked sodium hyaluronate gel can be obtained by the prior art method, for example, dissolving the non-cross-linked sodium hyaluronate solvent in a sodium hydroxide solution, and then adding a cross-linking agent such as 1,4-butanediol diglycidyl ether (BDDE). After the cross-linking reaction is completed, the reaction system is post-treated to obtain the cross-linked sodium hyaluronate gel. It should be noted that the content of the cross-linked sodium hyaluronate gel refers to the weight (mg / mL) of the cross-linked sodium hyaluronate contained in the unit volume of the composition; the degree of cross-linking can be calculated by the following formula: Degree of cross-linking = total moles of cross-linking agent / total moles of N-acetyl-D-glucosamine; It should be noted that the total moles of molecular cross-linking agent refers to the total moles of effectively grafted cross-linking agent, rather than the total moles of added cross-linking agent, because the grafting rate of the cross-linking agent is usually low and difficult to measure. Therefore, the cross-linking degree is generally measured directly using instruments during the experiment.

[0022] In the present invention, the sodium hyaluronate thiolated derivative solution is a precursor of the disulfide cross-linked sodium hyaluronate gel, which is oxidized to form a disulfide cross-linked sodium hyaluronate gel. The oxidation process is carried out in an aerobic environment. The general source of oxygen in the aerobic environment is oxygen in the air or dissolved oxygen in the solution during the mixing process. The preparation method of the disulfide cross-linked sodium hyaluronate gel can be obtained by referring to the prior patent CN118406258A, and Shu et al., Biomacromolecules 2002, 3: 1304-1311 and other prior documents. It should be noted that the molecular weight of the sodium hyaluronate disaccharide structural unit is about 400, and each disaccharide unit contains a carboxyl group that can be thiolated, that is, each gram of hyaluronic acid contains 2500 μmol of carboxyl groups that can be thiolated. Further, two thiols are oxidatively cross-linked to form a disulfide bond. For example, the sodium hyaluronate thiolated derivative solution with a modification degree of 1% is oxidatively cross-linked to obtain a cross-linked hyaluronic acid gel with a cross-linking degree of 0.5%. In addition, it should be noted that the thiol content refers to the micromolar number of thiol groups contained in each gram of thiol-containing sodium hyaluronate derivative (μmol / g), the degree of modification refers to the ratio of the thiol content to the carboxyl content, and the degree of modification value divided by 2 is the cross-linking degree of disulfide cross-linked sodium hyaluronate gel. The degree of modification refers to the ratio of the thiol content to the carboxyl content, and the degree of modification value divided by 2 is the cross-linking degree of disulfide cross-linked sodium hyaluronate gel.

[0023] In the present invention, the hyaluronic acid gel mixture is prepared by first dispersing cross-linked sodium hyaluronate gel particles in a sodium hyaluronate thiolated derivative solution, and then the sodium hyaluronate thiolated derivative solution undergoes an oxidation process to form a disulfide cross-linked hyaluronic acid gel (due to the occurrence of disulfide cross-linking, the mass before and after cross-linking remains unchanged, and the mass of the sodium hyaluronate thiolated derivative solution before cross-linking is equal to the mass of the disulfide cross-linked hyaluronic acid gel after cross-linking). Therefore, the hyaluronic acid gel mixture prepared by the method of the present invention is an integrated gel with high cohesion. At the same time, since the cross-linked sodium hyaluronate gel particles have a high elastic modulus, the hyaluronic acid gel mixture is provided with high elastic support performance and anti-enzymolysis ability; the hyaluronic acid gel mixture prepared by the method of the present invention also has better anti-enzymolysis ability.

[0024] In the present invention, after the cross-linked sodium hyaluronate gel particles are dispersed in the sodium hyaluronate thiolated derivative solution, sterilization and filling operations can be carried out. The oxidative cross-linking process occurs after filling, and the size and shape of the final product hyaluronic acid gel mixture are consistent with the filling container; it should be noted that sterilization refers to compliance with the microbiological standards for drugs or device products in this field (such as the Chinese Pharmacopoeia, the United States Pharmacopoeia, the European Pharmacopoeia or other national standards), and the sterilization process can be carried out in accordance with the GB18278.1-2015 standard. Specifically, sterilization refers to filling the mixed gel into a container and subjecting it to 121°C high saturated steam for 10 to 20 minutes.

[0025] In a specific embodiment, the particle size of the cross-linked sodium hyaluronate gel particles in step S1 ranges from 50 μm to 2500 μm. Preferably, D50 is not greater than 800 μm and / or D90 is not greater than 2000 μm.

[0026] In a specific embodiment, the cross-linking degree of the cross-linked sodium hyaluronate gel particles in step S1 is 1.0% to 20%, and the elastic modulus G' tested in the linear viscoelastic region with a shear strain γ=0.1% and a shear frequency of 1 Hz is not less than 700 Pa.

[0027] In a specific embodiment, the hyaluronic acid content in the cross-linked sodium hyaluronate gel particles in step S1 is 12 to 50 mg / mL or 16 to 30 mg / mL.

[0028] In a specific embodiment, the hyaluronic acid content in the thiolated sodium hyaluronate derivative solution in step S2 is 0.2-10 mg / mL, and the pH value is 6.8-7.6. It should be noted that the pH of the system can be adjusted and maintained by, for example, adding a phosphate buffer solution.

[0029] In a specific embodiment, the cross-linking degree of disulfide-cross-linked sodium hyaluronate gel in the hyaluronic acid gel mixture obtained in step S3 is 0.05% to 2.5% or 0.1% to 1.0%.

[0030] In a specific embodiment, in the hyaluronic acid gel mixture obtained in step S3, the mass ratio of cross-linked sodium hyaluronate gel particles to disulfide bond cross-linked sodium hyaluronate gel is 19:1 to 1:1. It should be noted that the mass ratio of the cross-linked sodium hyaluronate gel particles to the disulfide cross-linked sodium hyaluronate gel in the present invention can be adjusted according to clinical needs. For example, when used for medical cosmetic purposes, it is necessary to increase the volume of the skin or tissue for tissue shaping, especially when shaping the dorsum of the nose and / or the root of the nose and the mandibular part, the material is required to have strong bone support performance and high cohesion. A combination with a relatively high proportion of cross-linked sodium hyaluronate gel particles can be selected, such as a cross-linked sodium hyaluronate gel particle and a structural enhancement gel mass ratio of 19:1 to 8:2, which is usually injected with a 27G needle; for example, when used for prosthetic material applications such as osteoarthritis viscosity enhancement treatment, soft tissue wrinkle filling, gingival atrophy filling treatment, and increasing sphincter volume, the mass ratio of cross-linked sodium hyaluronate gel particles and disulfide cross-linked sodium hyaluronate gel can be designed to be between 19:1 and 1:1 according to specific needs. DETAILED DESCRIPTION

[0031] The technical solutions in the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0032] Example 1 Preparation of BDDE cross-linked sodium hyaluronate gel: Take 10g of non-cross-linked sodium hyaluronate (1500KDa), dissolve it in 100g of sodium hydroxide solution (1%), add 0.5g of cross-linking agent 1,4-butanediol diglycidyl ether (BDDE), heat in a 50℃ water bath, cross-link for 2h, and dialyze in neutral phosphate buffer for 48-72h after cross-linking. By controlling the water absorption and swelling rate, a BEED cross-linked sodium hyaluronate gel with a content of 23mg / ml is obtained, and the cross-linking degree is measured to be 1.13%.

[0033] Example 2 Preparation of DVS cross-linked sodium hyaluronate gel: Take 10g of non-cross-linked sodium hyaluronate (1500KDa), dissolve it in 100g of sodium hydroxide solution (1%), add 0.5g of cross-linking agent divinyl sulfone (DVS), heat in a 50℃ water bath, cross-link for 2h, and dialyze in neutral phosphate buffer for 48-72h after cross-linking. By controlling the water absorption and swelling rate, a DVS cross-linked sodium hyaluronate gel with a content of 23mg / ml is obtained, and the cross-linking degree is measured to be 1.51%.

[0034] Example 3 Preparation of Lysine Cross-linked Sodium Hyaluronate Gel: Take 10g of non-cross-linked sodium hyaluronate (400KDa) and 0.2g of lysine, dissolve in 150g of purified water, stir at 25℃ until dissolved, adjust pH to 4 with 0.1mol / L hydrochloric acid, pre-dissolve 1.0g of 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride (DMTMM) with 10g of purified water, add to the above sodium hyaluronate solution, stir at 25℃ for 24 hours. Place in neutral phosphate buffer for dialysis for 48-72 hours, and obtain lysine cross-linked sodium hyaluronate gel with a content of 23mg / ml by controlling the water absorption swelling rate, and the cross-linking degree is 1.20%.

[0035] Example 4 Preparation of cross-linked sodium hyaluronate gel: The cross-linked sodium hyaluronate gel in this embodiment is obtained by disulfide cross-linking and is used as the encapsulated cross-linked sodium hyaluronate particles. It is prepared by the method reported by Shu et al. (Shu et al., Biomacromolecules 2002, 3: 1304-1311), specifically: 10.0 g of sodium hyaluronate (MW 200 kDa) is dissolved in 100 mL of 40° C. distilled water, and an appropriate amount of 0.1 N hydrochloric acid is added to adjust the pH value of the solution to 4.75, and 3.2 g of Sulfo-NHS (N-hydroxysulfosuccinimide), 16.8 g of cystamine dihydrochloride, and 1.2 g of EDCI (1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride) solid are added respectively, stirred to dissolve, and an appropriate amount of acid or base (0.1 N hydrochloric acid or sodium hydroxide) is added to keep the pH value of the reaction solution stable at 4.75, and the reaction is stirred overnight. 1.0 N sodium hydroxide was added to adjust the pH of the reaction solution to 8.5 to terminate the reaction. Then 5.0 g of dithiothreitol was added, stirred to dissolve, and reacted for 4 hours. Then, 1.0 N hydrochloric acid was added to adjust the pH value of the reaction solution to 3.0, and the solution was placed in a dialysis bag with a molecular weight cutoff of 10 kDa, and then dialyzed and purified with a mixed solution of 0.001 N hydrochloric acid and 0.2 N sodium chloride. The purification process of the final product was tracked by gel permeation chromatography (GPC) until the impurity absorption peak was no longer visible, and a sodium hyaluronate thiolated derivative solution was obtained. After further freeze drying, a sodium hyaluronate thiolated derivative freeze-dried product was obtained. 5.0 g of the sodium hyaluronate thiolated derivative freeze-dried product was taken, and a phosphate buffer solution was added to prepare a 16 mg / ml solution. The pH was adjusted to about 7.2, and the solution was placed at 40°C for 7 days to obtain a 16 mg / ml disulfide bond cross-linked sodium hyaluronate acid gel, the thiol content of which was 51 μmol / g, and the calculated modification degree was 2.04%, and the cross-linking degree was 1.02%. The same method can be used to obtain 23 mg / ml and 30 mg / ml cross-linked sodium hyaluronate acid gels, both of which have a cross-linking degree of 1.02%. By adjusting the material ratio, a similar method can be used to prepare cross-linked sodium hyaluronan gels with thiol contents of 149 μmol / g (cross-linking degree of 2.98%) and 376 μmol / g (cross-linking degree of 7.52%), a total of 9 groups, as shown in Table 1.

[0036] Table 1 .

[0037] Example 5 Preparation of sodium hyaluronate thiolated derivative solution: The thiolated sodium hyaluronate derivative solution is prepared by the method reported by Shu et al. (Shu et al., Biomacromolecules 2002, 3:1304-1311) using sodium hyaluronate with a molecular weight of 200 KDa as a raw material. Specifically, 10.0 g of sodium hyaluronate (MW 200 kDa) is dissolved in 100 mL of 40°C distilled water, and an appropriate amount of 0.1 N hydrochloric acid is added to adjust the pH value of the solution to 4.75. 0.8 g of Sulfo-NHS, 8.4 g of cystamine dihydrochloride, and 0.3 g of EDCI solid are added, stirred and dissolved, and an appropriate amount of acid or base (0.1 N hydrochloric acid or sodium hydroxide) is added to keep the pH value of the reaction solution stable at the aforementioned specific value, and the reaction is stirred overnight. 1.0 N sodium hydroxide is added to adjust the pH of the reaction solution to 8.5 to terminate the reaction. Then 5.0 g of dithiothreitol is added, stirred and dissolved, and reacted for 4 hours. Then, 1.0 N hydrochloric acid was added to adjust the pH value of the reaction solution to 3.0, and the solution was placed in a dialysis bag with a molecular weight cutoff of 10 kDa, and then dialyzed and purified with a mixed solution of 0.001 N hydrochloric acid and 0.2 N sodium chloride. The purification process of the final product was tracked by gel permeation chromatography (GPC) until the impurity absorption peak was no longer visible, and a sodium hyaluronate thiolated derivative solution was obtained, with a thiol content of 5.1 μmol / g (cross-linking degree after cross-linking was 0.1%). Further, phosphate buffer was used to prepare 0.5 mg / ml, 2 mg / ml, and 4 mg / ml solutions. By adjusting the material ratio, a similar method can be used to prepare sodium hyaluronate thiolated derivative solutions with thiol contents of 25.2 μmol / g (cross-linking degree after cross-linking was 0.5%), 50.1 μmol / g (cross-linking degree after cross-linking was 1.0%), a total of 9 groups, as shown in Table 2, for standby use.

[0038] Table 2 .

[0039] Example 6 Preparation of hyaluronic acid gel mixture: S1. Take 18 g of the cross-linked sodium hyaluronate gel prepared in Example 1 and crush it to obtain gel particles with a D50 of 400 μm and a D90 of 850 μm; S2, taking the sodium hyaluronate thiolated derivative solution prepared in Group 5 of Example 5, adjusting the pH to 7.2 with phosphate buffer, taking 2 g of the pH-adjusted solution, adding the cross-linked sodium hyaluronate gel particles in step S1 and mixing evenly; S3. Fill the mixed system in S2 into a 1 ml pre-filled syringe and sterilize it by moist heat. After 2 days, the sodium hyaluronate thiolated derivative solution undergoes an oxidation process to form a disulfide-bond cross-linked sodium hyaluronate gel, thereby obtaining a hyaluronic acid gel mixture.

[0040] Example 7 Preparation of hyaluronic acid gel mixture: S1. Take 18 g of the cross-linked sodium hyaluronate gel prepared in Example 2, and crush it to obtain gel particles with a D50 of 400 μm and a D90 of 850 μm; S2, taking the sodium hyaluronate thiolated derivative solution prepared in Group 5 of Example 5, adjusting the pH to 7.2 with phosphate buffer, taking 2 g of the pH-adjusted solution, adding the cross-linked sodium hyaluronate gel particles in step S1 and mixing evenly; S3. Fill the mixed system in S2 into a 1 ml pre-filled syringe and sterilize it by moist heat. After 2 days, the sodium hyaluronate thiolated derivative solution undergoes an oxidation process to form a disulfide-bond cross-linked sodium hyaluronate gel, thereby obtaining a hyaluronic acid gel mixture.

[0041] Example 8 Preparation of hyaluronic acid gel mixture: S1. Take 18 g of the cross-linked sodium hyaluronate gel prepared in Example 3 and crush it to obtain gel particles with a D50 of 400 μm and a D90 of 850 μm; S2, taking the sodium hyaluronate thiolated derivative solution prepared in Group 5 of Example 5, adjusting the pH to 7.2 with phosphate buffer, taking 2 g of the pH-adjusted solution, adding the cross-linked sodium hyaluronate gel particles in step S1 and mixing evenly; S3. Fill the mixed system in S2 into a 1 ml pre-filled syringe and sterilize it by moist heat. After 2 days, the sodium hyaluronate thiolated derivative solution undergoes an oxidation process to form a disulfide-bond cross-linked sodium hyaluronate gel, thereby obtaining a hyaluronic acid gel mixture.

[0042] The information of the hyaluronic acid gel mixture cross-linked sodium hyaluronate gel particles and the disulfide bond cross-linked sodium hyaluronate gel in Examples 6 to 8 is shown in Table 3.

[0043] Table 3 .

[0044] Example 9 Preparation of hyaluronic acid gel mixture: S1. Take 18 g of the cross-linked sodium hyaluronate gel prepared in Group 1 of Example 4, and crush it to obtain gel particles with a D50 of 400 μm and a D90 of 850 μm; S2, taking the sodium hyaluronate thiolated derivative solution prepared in Group 5 of Example 5, adjusting the pH to 7.2 with phosphate buffer, taking 2 g of the pH-adjusted solution, adding the cross-linked sodium hyaluronate gel particles in step S1 and mixing evenly; S3. Fill the mixed system in S2 into a 1 ml pre-filled syringe and sterilize it by moist heat. After 2 days, the sodium hyaluronate thiolated derivative solution undergoes an oxidation process to form a disulfide-bond cross-linked sodium hyaluronate gel, thereby obtaining a hyaluronic acid gel mixture.

[0045] Examples 10-17 Preparation of hyaluronic acid gel mixture: On the basis of Example 9, in step S1, the cross-linked sodium hyaluronate gels obtained from other groups in Example 4 were used respectively, and with other preparation conditions unchanged, Examples 10 to 17 were obtained, as shown in Table 4.

[0046] Example 18 Preparation of hyaluronic acid gel mixture: S1. Take 18 g of the cross-linked sodium hyaluronate gel prepared in Group 5 of Example 4, and crush it to obtain gel particles with a D50 of 400 μm and a D90 of 850 μm; S2, taking the sodium hyaluronate thiolated derivative solution prepared in Group 1 of Example 5, adjusting the pH to 7.2 with phosphate buffer, taking 2 g of the pH-adjusted solution, adding the cross-linked sodium hyaluronate gel particles prepared in step S1 and mixing evenly; S3. Fill the mixed system in S2 into a 1 ml pre-filled syringe and sterilize it by moist heat. After 2 days, the sodium hyaluronate thiolated derivative solution undergoes an oxidation process to form a disulfide-bond cross-linked sodium hyaluronate gel, thereby obtaining a hyaluronic acid gel mixture.

[0047] Examples 19-25 Preparation of hyaluronic acid gel mixture: On the basis of Example 18, in step S2, the cross-linked sodium hyaluronate gels obtained from other groups in Example 5 were used respectively, and with other preparation conditions unchanged, Examples 19 to 25 were obtained, as shown in Table 4.

[0048] The information of the cross-linked sodium hyaluronate gel particles and the disulfide bond cross-linked sodium hyaluronate gel in the hyaluronic acid gel mixture obtained in Examples 9 to 25 is shown in Table 4.

[0049] Table 4 .

[0050] Example 26 Preparation of hyaluronic acid gel mixture: S1. Take 19 g of the cross-linked sodium hyaluronate gel prepared in Group 5 of Example 4, and crush it to obtain gel particles with a D50 of 400 μm and a D90 of 850 μm; S2, taking the sodium hyaluronate thiolated derivative solution prepared in Group 5 of Example 5, adjusting the pH to 7.2 with phosphate buffer, taking 1 g of the pH-adjusted solution, adding the cross-linked sodium hyaluronate gel particles in step S1 and mixing evenly; S3. Fill the mixed system in S2 into a 1 ml pre-filled syringe and sterilize it by moist heat. After 2 days, the sodium hyaluronate thiolated derivative solution undergoes an oxidation process to form a disulfide-bond cross-linked sodium hyaluronate gel, thereby obtaining a hyaluronic acid gel mixture.

[0051] Examples 27-29 Preparation of hyaluronic acid gel mixture: On the basis of Example 26, the mass ratio of the alternating sodium hyaluronate gel particles and the disulfide-bond cross-linked sodium hyaluronate gel was adjusted, and with other preparation conditions unchanged, Examples 27 to 29 were obtained, as shown in Table 5.

[0052] The information of the cross-linked sodium hyaluronate gel particles and the disulfide bond cross-linked sodium hyaluronate gel in the hyaluronic acid gel mixtures obtained in Examples 13 and 26 to 29 is shown in Table 5.

[0053] Table 5

[0054] The mass of the disulfide-bond cross-linked sodium hyaluronate gel is the mass of the sodium hyaluronate thiolated derivative solution with a pH value of 7.2 added in step S2.

[0055] Comparative Example 1: S1. Take 18 g of the cross-linked sodium hyaluronate gel prepared in Example 1 and crush it to obtain gel particles with a D50 of 400 μm and a D90 of 850 μm; S2. Fill the gel of S1 into a 1 ml prefilled syringe and sterilize it by moist heat to obtain the sample of Comparative Example 1.

[0056] Comparative Example 2: S1. Take 18 g of the cross-linked sodium hyaluronate gel prepared in Example 2, and crush it to obtain gel particles with a D50 of 400 μm and a D90 of 850 μm; S2. Fill the gel of S1 into a 1 ml prefilled syringe and sterilize it by moist heat to obtain the sample of Comparative Example 2.

[0057] Comparative Example 3: S1. Take 18 g of the cross-linked sodium hyaluronate gel prepared in Example 3 and crush it to obtain gel particles with a D50 of 400 μm and a D90 of 850 μm; S2. Fill the gel of S1 into a 1 ml prefilled syringe and sterilize it by moist heat to obtain the sample of Comparative Example 3.

[0058] Comparative Example 4: S1. Take 18 g of the cross-linked sodium hyaluronate gel prepared in Group 5 of Example 4, and crush it to obtain gel particles with a D50 of 400 μm and a D90 of 850 μm; S2. Fill the gel of S1 into a 1 ml prefilled syringe and sterilize it by moist heat to obtain the sample of Comparative Example 4.

[0059] Comparative Example 5: S1. Take 18 g of the cross-linked sodium hyaluronate gel prepared in Example 1 and crush it to obtain gel particles with a D50 of 600 μm and a D90 of 1500 μm; S2, dissolving non-cross-linked sodium hyaluronate (1500 KDa) in isotonic phosphate buffer, adjusting the content to 20 mg / ml, adjusting the pH to 7.2, taking 2 g of the pH-adjusted solution and mixing it evenly with the cross-linked sodium hyaluronate gel particles obtained in S1; S3. Fill the mixed system in S2 into a 1 ml prefilled syringe and sterilize it by wet heat to obtain a comparative example 5 sample.

[0060] Comparative Example 6: S1. Take 18 g of the cross-linked sodium hyaluronate gel prepared in Example 2 and crush it to obtain gel particles with a D50 of 600 μm and a D90 of 1500 μm; S2, dissolving non-cross-linked sodium hyaluronate (1500 KDa) in isotonic phosphate buffer, adjusting the content to 20 mg / ml, adjusting the pH to 7.2, taking 2 g of the pH-adjusted solution and mixing it evenly with the cross-linked sodium hyaluronate gel particles obtained in S1; S3. Fill the mixed system in S2 into a 1 ml prefilled syringe and sterilize by moist heat to obtain the sample of Comparative Example 6.

[0061] Comparative Example 7: S1. Take 18 g of the cross-linked sodium hyaluronate gel prepared in Example 3 and crush it to obtain gel particles with a D50 of 600 μm and a D90 of 1500 μm; S2, dissolving non-cross-linked sodium hyaluronate (1500 KDa) in isotonic phosphate buffer, adjusting the content to 20 mg / ml, adjusting the pH to 7.2, taking 2 g of the pH-adjusted solution and mixing it evenly with the cross-linked sodium hyaluronate gel particles obtained in S1; S3. Fill the mixed system in S2 into a 1 ml prefilled syringe and sterilize it by moist heat to obtain the sample of Comparative Example 7.

[0062] Comparative Example 8: S1. Take 18 g of the cross-linked sodium hyaluronate gel prepared in Group 5 of Example 4, and crush it to obtain gel particles with a D50 of 600 μm and a D90 of 1500 μm; S2, dissolving non-cross-linked sodium hyaluronate (1500 KDa) in isotonic phosphate buffer, adjusting the content to 20 mg / ml, adjusting the pH to 7.2, taking 2 g of the pH-adjusted solution and mixing it evenly with the cross-linked sodium hyaluronate gel particles obtained in S1; S3. Fill the mixed system in S2 into a 1 ml prefilled syringe and sterilize it by wet heat to obtain the sample of Comparative Example 8.

[0063] Comparative Example 9: S1. Take 10g of non-cross-linked sodium hyaluronate (1500KDa), dissolve it in 100g of sodium hydroxide solution (1%), add 0.5g of cross-linking agent 1,4-butanediol diglycidyl ether (BDDE), heat in a 50℃ water bath, cross-link for 2h, and dialyze in neutral phosphate buffer for 72h after cross-linking. By controlling the dialysis time, the first BDDE cross-linked sodium hyaluronate gel is obtained, with a content of 23mg / ml; Take 10g of non-cross-linked sodium hyaluronate (1500KDa), dissolve it in 100g of sodium hydroxide solution (1%), add 0.05g of cross-linking agent 1,4-butanediol diglycidyl ether (BDDE), heat in a 50℃ water bath, cross-link for 2h, dialyze in neutral phosphate buffer for 72h after cross-linking, and obtain the second BDDE cross-linked sodium hyaluronate gel by controlling the dialysis time, with a content of 23mg / ml; The first and second portions of BDDE cross-linked sodium hyaluronate gel were respectively taken and crushed to obtain gel particles with a D50 of 600 μm and a D90 of 1500 μm; S2: Take 18 g of the first portion of BDDE cross-linked sodium hyaluronate gel particles and 2 g of the second portion of BEED cross-linked sodium hyaluronate gel particles, mechanically stir and mix well; S3: The mixed gel of S2 was filled into a 1 ml pre-filled syringe and sterilized by moist heat to obtain the sample of Comparative Example 9.

[0064] Comparative Example 10: S1. Take the cross-linked sodium hyaluronate gel prepared in Group 5 of Example 4, and crush it to obtain gel particles with a D50 of 600 μm and a D90 of 1500 μm; S2, taking the thiolated hyaluronic acid solution obtained before freeze-drying prepared in Group 2 of Example 4, adjusting the pH to 7.2 with phosphate buffer, oxidizing to form a disulfide-bond cross-linked sodium hyaluronate gel, and crushing to obtain gel particles; S3. Take 18 g of the gel particles of S1 and 2 g of the gel particles of S2, stir mechanically to mix them evenly, and fill the mixed gel particles into a 1 ml prefilled syringe, sterilize them by wet heat, and obtain the sample of Comparative Example 10.

[0065] Comparative Example 11: S1. Dissolve 2 g of non-cross-linked hyaluronic acid with a molecular weight of 1500 KDa in 200 mL of 2% sodium chloride solution, add 400 mL of ethanol while stirring, collect the flocculent precipitate, squeeze it dry, add 100 mL of ethanol, let it stand for 12 hours, extract excess water, filter, remove the residual ethanol in the precipitate under reduced pressure, and crush the precipitate to obtain non-cross-linked sodium hyaluronate particles with a D50 of 600 μm and a D90 of 1500 μm; S2. Take the sodium hyaluronate thiolated derivative solution prepared in Group 5 of Example 5, adjust the pH to 7.2 with phosphate buffer, take 2 g of the pH-adjusted solution, add the non-cross-linked sodium hyaluronate particles in step S1 and mix well; S3. Fill the mixed system in S2 into a 1 ml prefilled syringe and sterilize it by moist heat. After 2 days, the sodium hyaluronate thiolated derivative solution undergoes an oxidation process to form a disulfide-bond cross-linked sodium hyaluronate gel, thereby obtaining the sample of Comparative Example 11.

[0066] Test Example 1 Gel Viscoelasticity: Viscoelasticity test method: 1 g of each example and comparative example sample was taken and tested using a rheometer (Anton Paar, MCR301). A flat plate with a diameter of 50 mm was selected, the plate spacing was set to 0.5 mm, the test temperature was 25°C, the shear strain γ = 0.1%, 1 Hz, and the elastic modulus (G´) and viscous modulus (G″) were tested.

[0067] The elastic modulus G' and viscous modulus G" of the samples prepared in Examples 6 to 29 and Comparative Examples 1 to 11 were tested, and the test results are shown in Table 6 below.

[0068] Table 6 .

[0069] As can be seen from Table 6, the gel compositions prepared in Examples 6 to 29 have the advantages of high elastic modulus and high viscosity modulus, so that they have good support and resistance to enzymolysis. Comparative Examples 1 to 4 have high elastic modulus, but their viscosity modulus is low and their support is poor. Comparative Examples 5 to 8 are based on Comparative Examples 1 to 4, and non-cross-linked hyaluronic acid is added to increase the viscosity modulus to a certain extent, but its viscosity modulus is still low and its support is still poor; Comparative Examples 9 to 10, cross-linked sodium hyaluronate gel with good elasticity and cross-linked sodium hyaluronate gel with good viscosity are mixed to prepare a gel with balanced elasticity and viscosity, but its viscosity modulus is still lower than that of each embodiment; Comparative Example 11 uses disulfide cross-linked sodium hyaluronate gel to wrap non-cross-linked sodium hyaluronate particles, and the elastic modulus and viscosity modulus of the mixture are both low. It is speculated that the non-cross-linked sodium hyaluronate particles partially absorb the water in the sodium hyaluronate thiolated derivative solution in the process of forming disulfide cross-links, resulting in partial dissolution.

[0070] Test Example 2 Gel cohesion test: The test method described in the reference (HEMA SUNDARAM et al., Plast Reconstr Surg, 2015, 136(4): 678-686) is as follows: take 1 g of gel sample, use a syringe equipped with a thin needle to draw a small amount (about 0.2 ml) of 2% toluidine blue solution and insert it into the bottom of the sample, slowly push the toluidine blue solution and gradually pull out the needle until all the samples are stained, and let it stand for 3 min after staining to ensure uniform staining of the samples; push the gel (without the injection needle) into a beaker containing 700 ml of purified water at a fixed speed of 400 mm / min at a distance of 2 cm from the water surface, set the magnetic stirring speed to 160 r / min, and the stirring bar length to 2.5 cm; start recording and taking pictures after the gel is squeezed out, and the picture taking time points are 15, 70, and 95 s after the start, and take 3 pictures for each sample at each time point. Ten people independently scored the cohesion of each image according to five different states of the gel (1 point - gel is completely dispersed; 2 points - gel is partially dispersed; 3 points - gel is partially dispersed and partially cohesive; 4 points - gel is mostly cohesive; 5 points - gel is completely cohesive) and calculated the average value.

[0071] The cohesion test results of the samples prepared in Examples 6 to 29 and Comparative Examples 1 to 11 are shown in Table 7.

[0072] Table 7 .

[0073] As can be seen from Table 7, the gel compositions prepared in Examples 6 to 29 have very high cohesion, and even after stirring for 95 seconds, they still maintain good cohesion, and the cohesion scores are all greater than 4 points. Comparative Examples 1 to 4 are single-item cross-linked sodium hyaluronate gels, which have very poor cohesion and are completely dispersed after stirring for 15 seconds; Comparative Examples 5 to 8 have improved cohesion after adding non-cross-linked sodium hyaluronate, and the gel is partially dispersed after stirring for 15 seconds; Comparative Examples 9 to 10 have further improved cohesion after mixing low-cross-linked cross-linked sodium hyaluronate gels, and the gel is partially dispersed and partially cohesive after stirring for 15 seconds. The gel cohesion decreases significantly after continuing to stir for 95 seconds; Comparative Example 11 is a package of non-cross-linked sodium hyaluronate particles, which has good cohesion when stirred for 15 seconds, but the cohesion deteriorates and is completely dispersed after further stirring for 70 seconds and 95 seconds.

[0074] Test Example 3 Stability Test: Stability accelerated test conditions: 50°C, humidity 75%.

[0075] Dynamic viscosity test method: Take an appropriate amount of gel particles from each group of samples and test them according to the third rotational viscometer method of 0633 Viscosity Determination Method in the General Rules of Part IV of the 2020 Edition of the Pharmacopoeia of the People's Republic of China. The test conditions are a shear rate of not less than 0.25 Hz and (25±0.1)°C.

[0076] The gels prepared in Example 10, Example 13, Example 16 and Comparative Examples 1, 5 and 9 were placed in a temperature and humidity stability test chamber, and the dynamic viscosity of the samples was tested after 0 days, 137 days and 274 days of acceleration. The test results are shown in Table 8 below.

[0077] Table 8 .

[0078] Table 8 shows that Comparative Example 1 is a cross-linked sodium hyaluronate gel, and its dynamic viscosity is 42.11% after 274 days of accelerated stability. After adding non-cross-linked sodium hyaluronate to Comparative Example 2, the stability decreased, and its dynamic viscosity was only 35.42% after 274 days of accelerated stability. After Comparative Example 9 was mixed with a low-cross-linked sodium hyaluronate gel, the stability was improved, and its dynamic viscosity was 46.57% after 274 days of accelerated stability. After 274 days of accelerated stability in Example 10, Example 13, and Example 16, the viscosity retention value reached more than 90% of 0 days, indicating that the gel prepared by the present invention has good viscosity performance stability.

[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A hyaluronic acid gel mixture, characterized in that: It comprises mixed disulfide bond cross-linked sodium hyaluronate gel and cross-linked sodium hyaluronate gel particles, wherein the cross-linked sodium hyaluronate gel particles are dispersed in the disulfide bond cross-linked sodium hyaluronate gel; When the hyaluronic acid gel mixture is tested in a linear viscoelastic region with a shear strain of γ=0.1% and a shear frequency of 1 Hz, the elastic modulus G' of the hyaluronic acid gel mixture is not less than 650 Pa, and the viscous modulus is not less than 70 Pa.

2. The hyaluronic acid gel mixture according to claim 1, characterized in that The particle size of the cross-linked sodium hyaluronate gel particles ranges from 50 μm to 2500 μm.

3. The hyaluronic acid gel mixture according to claim 2, characterized in that In the cross-linked sodium hyaluronate gel particles, D50 is not greater than 800 μm and / or D90 is not greater than 2000 μm.

4. The hyaluronic acid gel mixture according to claim 1, characterized in that The hyaluronic acid content in the cross-linked sodium hyaluronate gel particles is 12 to 50 mg / mL or 16 to 30 mg / mL; The hyaluronic acid content in the disulfide bond cross-linked sodium hyaluronate gel is 0.2-10 mg / mL or 0.5-4 mg / mL.

5. The hyaluronic acid gel mixture according to claim 1, characterized in that The cross-linking degree of the cross-linked sodium hyaluronate gel particles is 1.0% to 20%; The cross-linking degree of the disulfide bond cross-linked sodium hyaluronate gel is 0.05% to 2.5% or 0.1% to 1.0%.

6. The hyaluronic acid gel mixture according to claim 1, characterized in that The mass ratio of the cross-linked sodium hyaluronate gel particles to the disulfide bond cross-linked sodium hyaluronate gel is 19:1 to 1:

1.

7. Use of the hyaluronic acid gel mixture according to any one of claims 1 to 6 in the preparation of medical products.

8. The use according to claim 7, characterized in that The medical products include products for closing retinal holes to treat rhegmatogenous retinal detachment, products for vitreous filling, products for viscoelastic treatment of osteoarthritis, products for soft tissue wrinkle filling, products for facial reshaping, and products for increasing sphincter volume.

9. A method for preparing the hyaluronic acid gel mixture according to any one of claims 1 to 6, characterized in that: The steps include: S1. crushing the cross-linked sodium hyaluronate gel into cross-linked sodium hyaluronate gel particles; S2, dispersing the cross-linked sodium hyaluronate gel particles obtained in step S1 in a solution of a thiolated sodium hyaluronate derivative; S3. The sodium hyaluronate thiolated derivative solution dispersed with cross-linked sodium hyaluronate gel particles obtained in step S2 is gradually subjected to an oxidation process to form a disulfide-cross-linked sodium hyaluronate gel, thereby obtaining a hyaluronic acid gel mixture, wherein the elastic modulus G' of the hyaluronic acid gel mixture tested in the linear viscoelastic region with a shear strain γ=0.1% and a shear frequency of 1 Hz is not less than 650 Pa, and the viscosity modulus is not less than 70 Pa.

10. The preparation method according to claim 9, characterized in that: The particle size range of the cross-linked sodium hyaluronate gel particles in step S1 is 50 μm to 2500 μm.

11. The preparation method according to claim 10, characterized in that: In the cross-linked sodium hyaluronate gel particles, D50 is not greater than 800 μm and / or D90 is not greater than 2000 μm.

12. The preparation method according to claim 9, characterized in that: The cross-linking degree of the cross-linked sodium hyaluronate gel particles in step S1 is 1.0% to 20%, and the elastic modulus G' tested in the linear viscoelastic region with a shear strain γ=0.1% and a shear frequency of 1 Hz is not less than 700 Pa.

13. The preparation method according to claim 9, characterized in that: The hyaluronic acid content in the cross-linked sodium hyaluronate gel particles in step S1 is 12 to 50 mg / mL or 16 to 30 mg / mL.

14. The preparation method according to claim 9, characterized in that: The hyaluronic acid content in the sodium hyaluronate thiolated derivative solution in step S2 is 0.2-10 mg / mL, and the pH value is 6.8-7.

6.

15. The preparation method according to claim 9, characterized in that: The cross-linking degree of the disulfide-bond cross-linked sodium hyaluronate gel in the hyaluronic acid gel mixture obtained in step S3 is 0.05% to 2.5% or 0.1% to 1.0%.

16. The preparation method according to claim 9, characterized in that: The hyaluronic acid gel mixture obtained in step S3, wherein the mass ratio of cross-linked sodium hyaluronate gel particles to disulfide bond cross-linked sodium hyaluronate gel is 19:1 to 1:1.

Citation Information

Patent Citations

  • Process for preparing crosslinked hyaluronic acid gel

    CN101056891A

  • Cross-linked gels of hyaluronic acid and products containing such gels

    US4582865A

  • Double-phase crosslinked sodium hyaluronate gel with controllable shearing viscosity, and preparation method and preparations thereof

    CN108250457A

  • Hyaluronic acid gel composition for negative-pressure multi-needle injection and preparation method therefor

    CN110812270A

  • Hyaluronic acid filler having high viscoelasticity and high cohesiveness

    CN112423798A